PENGARUH MEDIA PEMBELAJARAN BERBASIS WORDWALL TERHADAP MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK SMP IT SABBIHISMA PADANG - Nenesia Okvaiv Adesta; Martin Kustati; Nana Sepriyanti (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
This research arises due to the low enthusiasm and academic achievement of students in Islamic Religious Education (PAI), particularly in the material of Honesty and Justice, which still largely uses traditional teaching methods. The use of digital learning media, such as Wordwall, is expected to create a more engaging learning experience and increase student participation. The objective of this research is to assess the impact of using Wordwall-based learning media on the motivation and achievement of eighth-grade students at SMP IT Sabbihisma Padang. The method used is a quantitative approach with an experiment thru a pretest-posttest design with a control group. The research subjects consisted of 30 students divided into two groups: the experimental group (15 students) who learned using Wordwall and the control group (15 students) who received traditional teaching. Data were collected using learning outcome tests and motivation questionnaires that had been tested for validity and reliability. The analysis results show that the average learning outcomes of students in the experimental class increased from 67.53 to 85.73, or an increase of 18.20 points, while the control class increased from 71.00 to 83.00, or an increase of 12.00 points. Additionally, the learning motivation of students in the experimental class reached a level of 96.33% with a very high category, while the control class only reached 57.40% with a moderate category. Thus, the use of Wordwall-based learning media has proven to have a positive impact on the increase in motivation and achievement of students in Islamic Religious Education.